Common Side Effects With Glaucoma Medications - Michaelov, Evan (Canadian Eye Care Today, 2025)
Glaucoma is a progressive optic neuropathy that affects more than 400 000 Canadians and up to 111 million are expected to be afflicted with the disease worldwide by 2040. Despite trends toward increasing utility of laser and surgical interventions for glaucoma treatment, topical medications remain a mainstay of treatment. These medications often comprise the initial treatment alongside selective laser trabeculoplasty (in open angle subtypes). Additionally, given the progressive nature of glaucoma, many patients who undergo laser or surgery treatments may eventually require the use of topical medications. Although glaucoma drops are generally accepted as safe and low risk for patients, each type carries its own side effect profiles and contraindications. No glaucoma drop is completely benign and can significantly affect patient wellbeing if not selected correctly. Therefore, it is important for ophthalmologists and eye care professionals, who will undoubtedly have numerous glaucoma patients in their care, to be aware of common side effects and contraindications associated with ocular anti-hypertensive agents. This article will outline the side effects and contraindications of the ocular anti-hypertensive agents currently available in Canada.